Penghimpunan Zakat IMPLIKASI PROGRAM AGEN KEBAIKAN TERHADAP PENGHIMPUNAN DANA ZIS LAZ IZI JAWA TIMUR: IMPLIKASI PROGRAM AGEN KEBAIKAN TERHADAP PENGHIMPUNAN DANA ZIS LAZ IZI JAWA TIMUR - Ahmad Kani Hasbullah; Khusnul Fikriyah (CV ODIS, 2022)
Indonesia is a country with great zakat potential. However, the existing zakat potential cannot be collected to the maximum. One of the obstacles to the less than optimal collection of zakat funds in Indonesia is the lack of competent human resources (HR). The purpose of this study was to determine the effect of the agen kebaikan program on fundraising at the Indonesian Zakat Initiative in the East Java region and the effect on human resources at the Amil Zakat Institution. This study uses a qualitative method, namely by obtaining information data about the agen kebaikan program and reports on the collection of ZIS funds at the IZI Amil Zakat Institute in East Java, which are then expected to reveal the phenomena in this study in depth in order to draw conclusions. The results of this study show that the agen kebaikan program has positive implications for the collection of ZIS funds at IZI East Java. Obtaining funds from the agen kebaikan program is quite helpful in raising funds for the East Java ZIS IZI, and can be a forum for producing competent human resources (HR), especially for zakat amil institutions.